Association Between Preoperative Factors and In-hospital Mortality in Neonates After Cardiac Surgery in China - Hu, Renjie; Zhu, Hongbin; Qiu, Lisheng; Hong, Haifa; Xu, Zhiwei; Zhang, Haibo; Chen, Hao (Frontiers in Pediatrics, 2021)
Background: Little is known about preoperative factors affecting cardiac surgery outcomes of neonates in China. We sought to examine the association between characteristics of neonates with congenital heart disease and early postoperative outcomes after cardiac repair in a tertiary care paediatric hospital. Methods: A single-centre retrospective cohort study of neonates who underwent cardiac surgery between January 2006 and December 2019 was performed. Demographic, institutional, and surgical characteristics of neonates were examined and their association with in-hospital mortality was analysed using multivariable logistic regression models. Results: During the study period, we analysed the outcomes of 1078 neonates. In-hospital mortality decreased to 13.8% in the era 2017–2019. The overall in-hospital mortality rate was 16.3%. Normal weight at surgery (odds ratio [OR], 0.63; 95% confidence interval [CI], 0.47–0.85; P=0.003) was associated with lower mortality risk. Poor health status (emergent: OR, 3.11; 95% CI, 1.96–4.94; P<0.001; elective: OR, 1.63; 95% CI, 1.11–2.40; P=0.013), higher Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery (STAT) categories (STAT 5 category: OR, 2.58; 95% CI, 1.04–6.43; P=0.042), and limited individual surgeon experience (surgeon with 5–10 operations per year: OR, 1.43; 95% CI, 1.06–1.95; P=0.021) were associated with higher odds of early death. Conclusion: In-hospital mortality after neonatal cardiac surgery remained high in our centre over the past 10 years. Some preoperative aspects, including low- weight at surgery, poor health status, increased surgical complexity and limited surgeon experience were significantly associated with higher mortality. Based on the observed associations, the necessary practices to be modified, especially in preoperative care, should be identified and assessed in future research.